Current progress on wire-arc and welding-based additive manufacturing with its potential application: a review - Mudzakkir Dioktyanto; Hidayat Abdullah; Yulia Puspa Dewi; Imam Nur Rokhim; Teguh Junian Kuswanto (Journal of Welding Technology, 2025)
Wire-Arc Additive Manufacturing (WAAM) is one of the leading metal additive manufacturing procedures for producing medium to large-scale components due to its high deposition rate, low material cost, and compatibility with common structural alloys. This paper review provides a focused and critical assessment of welding-based Additive Manufacturing (AM) technologies, particularly WAAM processes utilizing Gas Metal Arc Welding (GMAW), Gas Tungsten Arc Welding (GTAW), and Plasma Arc Welding (PAW). The scope covers the fundamental process principles, thermal–metallurgical behaviour, mechanical performance, and deposition control methods. The specific contribution of this review is: (i) explaining key process–structure–property relationships documented in recent studies, (ii) identifying core technological barriers—such as thermal distortion, porosity, residual stresses, and anisotropic microstructures—that limit industrial deployment, and (iii) outlining strategic future research directions that important for improving process stability and weld results. Key findings indicate that heat input management governs bead morphology, cooling rate, phase formation, and residual stress accumulation across multi-layer builds. Advances such as adaptive arc modes, interpass temperature control, closed-loop sensing, and hybrid subtractive–additive workflows have shown significant reductions in geometric deviation and defect formation. Nevertheless, reproducibility, dimensional accuracy, and mechanical property predictability remain persistent challenges. Overall, the review shows that integrating real-time monitoring, predictive simulation, alloy design tailored for WAAM, and intelligent control systems represents the most impactful pathway toward achieving certified and industrial-grade components.